Correlation between Lipid Accumulation Product with Fasting Blood Glucose and CRP in Obese Females - Natra Dias Surohadi; Dwi Retnoningrum; Meita Hendrianingtyas; Etika Ratna Noer; Ahmad Syauqi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Obesity is an excessive fat accumulation due to an imbalance between energy intake and consumption. Central obesity, represented by an increase in Waist Circumference (WC) and waist-to-hip ratio, is a predictor for obesity-related metabolic disorders and has replaced BMI to determine the clinical diagnosis of metabolic syndrome. Lipid accumulation product calculated from WC and fasting triglyceride concentration is presumed to be an alternative to measure excessive lipid accumulation and a marker to predict diabetes or cardiovascular risk. Lipid accumulation product is related to cardiovascular disease, diabetes, and metabolic syndrome and is preferable to BMI to identify diseases. It has been established that obesity and increased visceral adipocytes contribute to increased levels of some inflammatory proteins such as CRP. This study aimed to determine the correlation between LAP with FBG and CRP in obese females. This cross-sectional study involved female with obesity aged 35-50 years at Diponegoro National Hospital, Semarang, carried out from February to May 2021. Lipid accumulation product was calculated using LAP=(WC[cm]–58)×(TG[mmol/L]), TG and FBG levels were measured with the colorimetric enzymatic method, and CRP levels were analyzed with an immunoturbidimetric method using the chemical analyzer. The correlation between variables was analyzed using Pearson and Spearman correlation tests (p <0.05). CRP and FBG average levels were 3.546±2.6554 mg/dL and 83.1±11.363 mg/dL, respectively. There was a weak positive correlation between LAP with FBG (p=0.033; r=0.262) and LAP with CRP (p=0.04; r=0.251). Therefore, lipid accumulation products might influence FBG and CRP levels in the obese population